HUBUNGAN HIGIENE SANITASI KANDANG AYAM BROILER DENGAN PENYAKIT DERMATITIS KONTAK PADA PEKERJA KANDANG AYAM BROILER DI DESA BULAN BULAN KECAMATAN LIMA PULUH KABUPATEN BATU BARA - Ginting, Evfy Septriani (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
The purpose of this study was to look at the relationship between personal hygiene and cage sanitation and the preval_ence of dermatitis among broiler chicken farm workers in Bulan Bulan Village, Limapuluh District, Batu Bara Regency. This study used a cross-sectional design, with a sample size of 50 randomly selected respondents. Data collection methods or procedures are tools that researchers might employ to gather information. There are numerous data collection methods, including observation and measurement. Dermatitis occurred in 33 (66.0%) of the 36 respondents who did not maintain personal hygiene, while only 6 (12.0%) of the 14 respondents who did. Statistical analysis with the chi-square test revealed a p value of 0.001, demonstrating a significant link between personal hygiene and the occurrence of dermatitis. Cage conditions that are less than ideal, such as not cleaning every day and not employing sufficient personal protective equipment (PPE), have also been shown to raise the incidence of dermatitis in workers. The accumulation of chicken droppings in chicken coops promotes the spread of bacteria and insects, contributing to high incidence of dermatitis. This study revealed that proper personal hygiene and cage sanitation are critical to preventing dermatitis in chicken farm workers. Workers require education and training on the importance of personal hygiene and cleanliness in the cage, as well as regular implementation of sanitation measures to ensure a healthier and safer work environment.